Prognostic role of standard uptake value according to pathologic features of lung adenocarcinoma. Issue 5 (October 2022) - Bertoglio, Pietro; Ventura, Luigi; Aprile, Vittorio; Cattoni, Maria Angela; Nachira, Dania; Lococo, Filippo; Rodriguez Perez, Maria; Guerrera, Francesco; Minervini, Fabrizio; Gnetti, Letizia; Bacchin, Diana; Franzi, Francesca; et al.
Objective: To evaluate the influence of lung adenocarcinoma second predominant pattern on the maximal standard uptake value (SUVmax) and its prognostic effect in different histologic groups. Methods: We retrospectively collected surgically resected pathologic stage I and II lung adenocarcinoma from nine European institutions. Only patients who underwent preoperative PET-CT and with available information regarding SUVmax of T (SUVmaxT) and N1 (SUVmaxN1) component were included. Results: We enrolled 344 patients with lung adenocarcinoma. SUVmaxT did not show any significant relation according to the second predominant pattern ( p = 0.139); this relationship remained nonsignificant in patients with similar predominant pattern. SUVmaxT influenced the disease-free survival in the whole cohort ( p = 0.002) and in low- and intermediate-grade predominant pattern groups ( p = 0.040 and p = 0.008, respectively). In the high-grade predominant pattern cohort and in the pathologic N1 cases, SUVmaxT lost its prognostic power. SUVmaxN1 did not show any significant correlation with predominant and second predominant patterns and did not have any prognostic impact on DFS. Conclusions: SUVmaxT is influenced only by the adenocarcinoma predominant pattern, but not by second predominant pattern. Concurrently, in high-grade predominant pattern and pN1 group the prognostic power of SUVmaxT becomes nonsignificant.